Growth, distribution and poverty in Madagascar: learning from a microsimulation model in a general equilibrium framework - Cogneau, Denis; Robilliard, Anne-Sophie (International Food Policy Research Institute, 2000)
This paper presents an applied microsimulation model built on household data with explicit treatment of heterogeneity of skills, labor preferences and opportunities, and consumption preferences at the individual and/or household level, while allowing for an endogenous determination of relative prices between sectors. The model is primarily focused on labor markets and labor allocation at the household level, but consumption behavior is also modeled. Modeling choices are driven by a desire to make the best possible use of microeconomic information derived from household data. This framework supports analysis of the impact of different growth strategies on poverty and income distribution, without making use of the ""representative agent"" assumption. The model is built on household survey data and represents the behavior of 4,508 households. Household behavioral equations are estimated econometrically. Different sets of simulation are carried out to examine the comparative statics of the model and study the impact of different growth strategies on poverty and inequality. Simulation results show the potential usefulness of this class of models to derive both poverty and inequality measures and transition matrices without prior assumptions regarding the intra-group income distribution. Market clearing equations allow for the endogenous determination of relative prices between sectors. The impact of different growth strategies on poverty and inequality is complex given general equilibrium effects and the wide range of household positions in markets for factors and goods markets. Partial equilibrium analysis or the use of representative households would miss these effects.